Mediating role of access to finance on the relationship between strategic orientation attributes and SMEs performance in Nigeria - Ibrahim, Murtala Aminu; Mohd Shariff, Mohd Noor (Universiti Malaysia Sarawak, 2016)
In spite of recognized significant contribution of SMEs to nations’ economy, Nigerian SMEs performance is below expectation.This is because SMEs in Nigeria today faces severe limitations in financing, management skill, marketing, modern technology and technical expertise. The objective of this study is to investigate the mediating role of access to finance on the positive relationship between entrepreneurial orientation (EO), market orientation (MO), learning orientation (LO), technology orientation (TO) and SMEs performance in Nigeria.A sample size of 522 SMEs operating in Kano, Kaduna and Sokoto states of Nigeria were selected using stratified simple random sampling techniques.Partial Least Squares-Structural Equation Modelling was used to analyze the data.Hence, the data analysis was conducted using SmartPLS 3.0. The results of path analysis indicate that access to finance mediates the positive relationship between MO, LO, TO and the performance of small and medium enterprises in Nigeria.This is an important additional explanation for the existence of the relationship between these strategic orientations and firm performance.The results further suggest that SMEs need to use their strategic activities to improve their ability to obtain finances in order to perform well.Finally, recommendations for further research are also discussed.